PENERAPAN MODEL PEMBELAJARAN RADEC (READ, ANSWER, DISCUSS, EXPLAIN, AND CREATE) UNTUK MENINGKATKAN HASIL BELAJAR IPAS PESERTA DIDIK KELAS IVA UPT SPF SDN MELAYU MUHAMMADIYAH - Anita; Atika Hardianti Syam (STKIP Subang, 2024)
This research was based on the attitude of students who were less enthusiastic in learning process so that their learning outcomes were very low. This research was a classroom action research (CAR) that aimed to improve science learning outcomes through the implementation of RADEC learning model in class IVA of UPT SPF SDN Melayu Muhammadiyah. The subjects of this research were class IVA UPT SPF SDN Melayu Muhammadiyah consisted of 22 students. The techniques of data collection were observation and test (evaluation). The data obtained were analyzed using qualitative and quantitative analysis. The results of this study proved that the Read, Answer, Discuss, Explain, and Create (RADEC) learning model could improve students’ science learning outcomes. It could be proved from the average value of students learning outcomes in cycle I was 35 and the average value increased to 81.3 in cycle II. Moreover, the students were active in the learning process and they could think critically, collaborated, and communicated well.